Target Product Profile for an endometrial receptivity test: women's perspective. (October 2020) - Craciunas, Laurentiu; Pickering, Oonagh; Chu, Justin; Žurauskienė, Justina; Coomarasamy, Arri
Abstract: Objective: To assess the women's views in relation to the characteristics of an endometrial receptivity test in the context of recurrent miscarriage with an overarching aim to guide the development of a Target Product Profile (TPP) based on minimum acceptable ("worst-case") and ideal ("best-case") features. Study design: This was a descriptive cross-sectional study involving a total of 131 women who answered questions related to the development of an endometrial receptivity test between December 2017 and May 2018. Women attending the recurrent miscarriage clinic at the Tommy's National Centre for Miscarriage Research in Birmingham, United Kingdom, were invited to participate. Referral criteria included two or more miscarriages irrespective of the timing in relation to successful pregnancies. The 'best-case' (ideal) and 'worst-case' (minimum acceptable) thresholds were arbitrary set to satisfy at least 80% and 40% of responders, respectively. Results: The ideal endometrial receptivity test should be indicated after two miscarriages to comply with the wish of 80.9% (106 women) of responders. It should be performed in a window of three to four days within the menstrual cycle (93.2%; 122 women) and results should be available within one to two days (87.7%; 115 women). Invasiveness of testing should not extend beyond a vaginal examination (85.4%; 112 women). Repeating the test should not be required more than twice (96.1%; 125 women) and the results should remain useful for at least six menstrual cycles (89.3%; 117 women). The importance score given for the endometrium was weakly associated with the willingness to pay for testing; however, there was no evidence to suggest this correlation was different from 0 (Kendall's tau = 0.1101765, z = 1.4327, p-value = 0.1519; Spearman's rho = 0.1268444, S = 327136, p-value = 0.1488). Conclusions: Women understand the important role the endometrium plays for a successful pregnancy and they have specific views in relation to the indication, timing and invasiveness of testing, need for test repetition, validity of results and costs of testing.